(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
This study aimed to evaluate the impact of size heterogeneity on the growth and production economics of African Catfish (Clarias gariepinus). The experimental fish were divided into two treatment groups - homogenous and heterogonous - with different feeding time intervals morning hour (08.00am) afternoon hour (1:00pm) and evening hour (6:0pm) respectively. Each treatment had two replicates with 20 fish per replicate. The fish were fed with a commercial feed (coppens) at 5% for 8 weeks and 3% (for 8 weeks) of their body weight to the end of the experiment. The results showed significant differences (p<0.05) in the growth rate, and economic aspects of the experimental fish. The heterogeneous group had the highest growth rates in various parameters, while the homogenous group had the highest in most economic indices. The cost implication of feeding the fish varied significantly, with the highest cost at the prevailing market price for the homogenous group. The survival rate remained consistent across the two treatments. The length-weight regression analysis showed that the b-values of 2.112 (Homogenous) and 1.945 (Heterogeneous) exhibited negative allometric growth for the different treatments. The study also revealed a strong positive correlation coefficient for C. gariepinus, indicating a strong association between length and weight. The study also found significant differences in the total cost of feed consumed by the fish, indicating that despite differences in the cost of fish and feed used, the profit would still be high and the feeding methods used were also economical.